Unrecognized myocardial infarctions assessed by cardiovascular magnetic resonance are associated with the severity of the stenosis in the supplying coronary artery. Issue 1 (December 2015) - Hammar, Per; Nordenskjöld, Anna; Lindahl, Bertil; Duvernoy, Olov; Ahlström, Håkan; Johansson, Lars; Hadziosmanovic, Nermin; Bjerner, Tomas
Abstract Background A previous study has shown an increased prevalence of late gadolinium enhancement cardiovascular magnetic resonance (LGE CMR) detected unrecognized myocardial infarction (UMI) with increasing extent and severity of coronary artery disease. However, the coronary artery disease was evaluated on a patient level assuming normal coronary anatomy. Therefore, the aims of the present study were to investigate the prevalence of UMI identified by LGE CMR imaging in patients with stable angina pectoris and no known previous myocardial infarction; and to investigate whether presence of UMI is associated with stenotic lesions in the coronary artery supplying the segment of the myocardium in which the UMI is located, using coronary angiography to determine the individual coronary anatomy in each patient. Methods In this prospective multicenter study, we included patients with stable angina pectoris and without prior myocardial infarction, scheduled for coronary angiography. A LGE CMR examination was performed prior to the coronary angiography. The study cohort consisted of 235 patients (80 women, 155 men) with a mean age of 64.8 years. Results UMIs were found in 25 % of patients. There was a strong association between stenotic lesions (≥70 % stenosis) in a coronary artery and the presence of an UMI in the myocardial segments supplied by the stenotic artery; it was significantly more likely to have an UMI downstream a stenosis ≥ 70 % as compared to < 70 % (OR 5.1, CI 3.1-8.3, p  < 0.0001). 56 % of the UMIs were located in the inferior and infero-lateral myocardial segments, despite predominance for stenotic lesions in the left anterior descending artery. Conclusion UMI is common in patients with stable angina and the results indicate that the majority of the UMIs are of ischemic origin due to severe coronary atherosclerosis. In contrast to what is seen in recognized myocardial infarctions, UMIs are predominately located in the inferior and infero-lateral myocardial segments. Trial registration The PUMI study is registered at ClinicalTrials.gov (NCT01257282 ).